GAMBARAN, PENGARUH, DAN KEDUDUKAN DEMOKRASI INDONESIA DI ERA MODERN DALAM SUDUT PANDANG MASYARAKAT - Hutabarat, Dany Try Hutama; Rambe, Nurhaliza; Ayu, Erra; Andrian, Pandu; Ersa, Fikri; Arya, Dicky; Sujati, Cecep; Bintang, Muhammad; Arya, Ilham; Amri, Juheri; Opri, Gilang; Pratama, Nanda; Irawan, Iqbal (Transpublika Publisher, 2022)
The current study of democracy has been discussed in various book and journal studies. Not only that, democracy is also a topic of ideas that are always interesting to explore. The study of the picture, influence, and position of Indonesian democracy in the modern era from the public's point of view is no less important to be discussed. The study of looking for a figure of Indonesian democracy has never been completed. Democracy is not new but has gone through a long process, even considered as a form of government. Because of the large role of democracy in the structure of the state, education about Indonesian democracy is made. Democracy can also be seen as a phenomenon of power in a state institution in the political field where the greatest power is in the hands of the people. So, from the people's point of view, the position and influence of Indonesian democracy is one thing we know that democracy has a very important position and influence in the life of the nation and state.